Die Selbstevaluation im prozess- und lernerorientierten Fremdsprachenunterricht (Bedeutung, Ziele, Umsetzungsmöglichkeiten) - Chudak, Sebastian (Glottodidactica, 2000)
The article concerns the issue of evaluation in the process of teaching a foreign language as its inseparable component. So far evaluation has been perceived as a process having a great importance for the teacher who can use it as a tool for controlling whether his aims have been achieved or not, to plan further work in a better way etc. Such approach to the process of evaluation, however, is not too much beneficial. This is why this article concentrates on the learner’s self - evaluation as the best way to establish his own aims, monitoring his progress, reflection on the chosen method of work and the possibility of changing it according to his needs etc. So the article says about the value of self- evaluation, its aims and possibilities of realization. The problem discussed is especially interesting and valid in the context of changing the approach from the traditional one (concentrated on the outcome of the process of learning) to teaching aimed at learner autonomy (in which more attention is paid to the process of learning itself).